1997
DOI: 10.1002/(sici)1098-2264(199708)19:4<201::aid-gcc1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained nontumorigenic phenotype correlates with a largely stable chromosome content during long-term culture of the human keratinocyte line HaCaT

Abstract: Altered growth and differentiation and a highly abnormal karyotype are generally believed to be indicators for tumorigenic conversion of human cells. Inactivation of TP53 is supposedly one possible mechanism for accelerated genetic aberrations via reduced control of the genetic integrity. To examine the significance of this functional relationship, we investigated the long‐term development of the spontaneously immortalized human skin keratinocyte line HaCaT, carrying UV‐specific mutations in both alleles of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 42 publications
5
107
0
1
Order By: Relevance
“…Already a five-week-UVA-treatment is sufficient to induce tumorigenicity in three of the four populations. We previously showed that mere cultivation even for >6 years and >300 passages did not lead to tumorigenicity (Boukamp et al, 1997). Accordingly, mock-treated control cells remained nontumorigenic.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Already a five-week-UVA-treatment is sufficient to induce tumorigenicity in three of the four populations. We previously showed that mere cultivation even for >6 years and >300 passages did not lead to tumorigenicity (Boukamp et al, 1997). Accordingly, mock-treated control cells remained nontumorigenic.…”
Section: Discussionmentioning
confidence: 93%
“…These cells represent an early stage of skin carcinogenesis because they harbor UVB type-specific p53 mutations (Lehman et al, 1993) as well as some chromosomal abnormalities typical for human skin SCCs (Lehman et al, 1993;Boukamp et al, 1997;Popp et al, 2002). While the HaCaT cells remained nontumorigenic through long-term passaging, they became tumorigenic by transduction with the Harvey-ras oncogene, increased temperature or stroma modulating growth factors known to be relevant for tumorigenicity (Boukamp et al, 1990b(Boukamp et al, , 1995(Boukamp et al, , 1997Skobe and Fusenig, 1998;Obermueller et al, 2004). Thus, the intrinsic stable nontumorigenic phenotype, together with the sensitivity for tumorigenic conversion upon distinct changes, make HaCaT cells a highly suitable model to study the role of UVA in skin carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The HaCaT cells analyzed here are immortalized and non-transformed KCs with mutant p53 allelles-R282Q and H179Y-and the levels of the p53 proteins are extremely high. They are not a model for skin cancer, as they are able to differentiate in vitro, unable to form colony assays in soft agar and do not generate tumors in nude mice in vivo (Boukamp et al, 1997;EM and RM, unpublished). However, the p53 missense mutations harbored by HaCaT alleles are indeed UVB signature mutations (Pfeifer and Besaratinia, 2009, and references therein).…”
Section: Activation Of Klf4 By Mutant P53mentioning
confidence: 99%
“…We have chosen the telomerase-immortalized retinal pigment epithelial cells (RPE hTert) because of their relatively normal and diploid karyotype, compared to cancer cells and other viral-protein immortalized cell types (Boukamp et al, 1997;Duensing and Munger, 2002). RPE hTert only harbors one balanced translocation between chromosomes 2 and X (Figure 5b, i).…”
Section: Lmp1 Overexpression Induces Chromosomal Aberrations In Rpe Cmentioning
confidence: 99%